Metode Demonstrasi Untuk Meningkatkan Hasil Belajar Siswa - TB Endayani; Cut Rina; Maya Agustina (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
This study discusses the implementation of demonstration methods to improve student learning outcomes. The library research method used a qualitative descriptive approach. The results of this study from several theses and journals show that demonstration methods can improve student learning outcomes. As for the obstacles faced by several writers Nyoman Kariasa, Asmiati, Yung Antonius, Mastar Asran, Abdussamad., Nurhayat, Syarifah Fadilah, Mutmainnah, Alisman, Siti Rofi'ah, Indri Sofatun, Syarianty Devi. namely the delivery of teacher material that is still lacking, and the lack of teaching aids available in the madrasah, and limited time is limited